Redresser les dispositions des enfants de milieux populaires et de leurs familles par l’éducation artistique et culturelle : les ambitions normalisatrices de deux dispositifs d’orchestres d’enfants à dimension sociale - Rémi Deslyper; Florence Eloy (Cahiers de la Recherche sur l'Education et les Savoirs)
Thought as carrying out a larger function than only the familiarisation with art and culture, the actors of artistic and cultural education (EAC) believe it also aims to contribute to individual development and the education of the citizen. Contrary to this salutary vision and from the study of two education programs for learning music through orchestral practice, this article seeks to show that the EAC’s will to transform can be analysed as a work of normalizing dominated people’s behaviours. First we will describe how the coordinators and teachers involved in the musical programs perceive the children from disadvantaged backgrounds; then we will study the dispositions the actors wish to pass on to the children through three aspects: the attitudes to time, the body and finally the reflexivity.